Systemic Overexpression of GDF5 in Adipocytes but Not Hepatocytes Alleviates High-Fat Diet-Induced Nonalcoholic Fatty Liver in Mice - Yan Yang; Wenting Zhang; Xiaohui Wu; Jing Wu; Chengjun Sun; Feihong Luo; Zhou Pei (Canadian Journal of Gastroenterology and Hepatology)
Objective. Our recent study demonstrated that growth differentiation factor 5 (GDF5) could promote white adipose tissue thermogenesis and alleviate high-fat diet- (HFD-) induced obesity in fatty acid-binding protein 4- (Fabp4-) GDF5 transgenic mice (TG). Here, we further investigated the effects of systemic overexpression of the GDF5 gene in adipocytes HFD-induced nonalcoholic fatty liver disease (NAFLD). Methods. Fabp4-GDF5 TG mice were administered an HFD feeding. NAFLD-related indicators associated with lipid metabolism and inflammation were measured. A GDF5 lentiviral vector was constructed, and the LO2 NAFLD cell model was induced by FFA solution (oleic acid and palmitic acid). The alterations in liver function, liver lipid metabolism, and related inflammatory indicators were analyzed. Results. The liver weight was significantly reduced in the TG group, which was in accordance with the significantly downregulated expression of TNFα, MCP1, Aim2, and SREBP-1c and significantly upregulated expression of CPT-1α and ACOX2 in TG mouse livers. Compared to that of cells in the FAA-free control group, LO2 cells with in situ overexpression of GDF5 developed lipid droplets after FFA treatment; the levels of triglycerides, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were significantly increased in both the GDF5 lentivirus and control lentivirus groups compared with those of the FAA-free group. Additionally, the levels of FAS, SREBP-1, CPT-1α, and inflammation-associated genes, such as ASC and NLRC4, were unaltered despite GDF5 treatment. Conclusion. Systemic overexpression of GDF5 in adipose tissue in vivo significantly reduced HFD-induced NAFLD liver damage in mice. The overexpression of GDF5 in hepatocytes failed to improve lipid accumulation and inflammation-related reactions induced by mixed fatty acids, suggesting that the protective effect of GDF5 in NAFLD was mainly due to the reduction in adipose tissue and improvements in metabolism. Hence, our study suggests that the management of NAFLD should be targeted to reduce the overall amount of body fat and improve metabolic status before the progression to nonalcoholic steatohepatitis occurs.